1993
DOI: 10.1128/aem.59.8.2501-2510.1993
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Ammonia Monooxygenase Inhibition in Nitrosomonas europaea by Hydrocarbons and Halogenated Hydrocarbons in an Optimized Whole-Cell Assay

Abstract: The inhibitory effects of 15 hydrocarbons and halogenated hydrocarbons on NH3 oxidation by ammonia monooxygenase (AMO) in intact cells of the nitrifying bacterium Nitrosomonas europaea were determined. Determination of AMO activity, measured as N02 production, required coupling of hydroxylamine oxidoreductase (HAO) activity with NH3-dependent NH20H production by AMO. Hydrazine, an alternate substrate for HAO, was added to the reaction mixtures as a source of reductant for AMO. Most inhibitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 25 publications
2
70
1
2
Order By: Relevance
“…The increased sensitivity of potential nitrification activity may be explained by the inhibitory effect of aliphatic compounds on the ammonia monooxygenase (AMO) enzyme. Keener and Arp [7] suggest that hydrocarbons cause inhibition of AMO through competitive or noncompetitive interactions with the enzyme. The competitive nature of the inhibitor generally decreases as molecular size increases (i.e., small hydrocarbon molecules are capable of competing with ammonia for the active binding site on the AMO enzyme).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased sensitivity of potential nitrification activity may be explained by the inhibitory effect of aliphatic compounds on the ammonia monooxygenase (AMO) enzyme. Keener and Arp [7] suggest that hydrocarbons cause inhibition of AMO through competitive or noncompetitive interactions with the enzyme. The competitive nature of the inhibitor generally decreases as molecular size increases (i.e., small hydrocarbon molecules are capable of competing with ammonia for the active binding site on the AMO enzyme).…”
Section: Discussionmentioning
confidence: 99%
“…The competitive nature of the inhibitor generally decreases as molecular size increases (i.e., small hydrocarbon molecules are capable of competing with ammonia for the active binding site on the AMO enzyme). Keener and Arp suggest that AMO inhibition by hydrocarbon could occur either by directly competing with ammonia at the AMO binding site for reducing equivalents or by binding to a hydrophobic region of the AMO enzyme and influencing enzyme turnover [7]. Polyaromatic hydrocarbons, such as naphthalene, also can irreversibly inhibit AMO [37].…”
Section: Discussionmentioning
confidence: 99%
“…Chem. 16,1997 J.L. Miller et al King et al [10] have also shown no effect of a chlorinated solvent on degradation of an organic substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the detection of both nitrite and nitrate in samples after 2 months of additional incubation and the growth of nitrifying bacteria in liquid culture medium indicate that inhibition of nitrification may similarly be due to this interaction with a key enzyme. Keener and Arp [16] have shown that the halogenated alkanes are noncompetitive substrates for AMO and have proposed a model of AMO that contains two substrate binding sites. In this model, one site will accommodate C 1 and C 2 hydrocarbons as well as NH 3 , while the other, more hydrophobic site has a wider substrate range that Effect of application solvents on nitrification Environ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation